Thoracoscopic tracheal reconstruction without surgical field intubation. Issue 4 (20th January 2016) - Zhao, Kejia; Mei, Jiandong; Hai, Yang; Liu, Chengwu; Ma, Lin; Liu, Lunxu
Abstract: A cross‐filed endotracheal intubation is usually applied to maintain single lung ventilation during both open and thoracoscopic tracheal resection and reconstruction. Herein, we report a case of thoracoscopic tracheal resection and reconstruction with interrupted ventilation via transoral endotracheal intubation in a patient with thoracic tracheal adenocarcinoma. Tracheal anastomosis was accomplished using a running suture with a 3‐0 Prolene stitch.